Hamster Hotal - "Daniels , Lucy" (Hodder Childrens books: London, 1996)
Mandy's grandparents are looking after a hamster - and they don't have a clue! Mandy promises to come and help out... This title is part of the "Animal Ark" series that provides animal stories for younger readers.
Keywords: English fiction - Book